Expanding the function $\ln(1+\operatorname{e}^x)$ into power series in terms of the Dirichlet eta function and the Stirling numbers of the second kind - Li, Wen-Hui; Lim, Dongkyu; Qi, Feng (Carpathian Mathematical Publications, 2024)
In the paper, using several approaches, the authors expand the composite function $\ln(1+\operatorname{e}^x)$ into power series around $x=0$, whose coefficients are expressed in terms of the Dirichlet eta function $η(1-n)$ and the Stirling numbers of the second kind $S(n,k)$.